Analyzing the Generic Structure Potential of Admission Notifications of Universities of Pakistan - Farooq, Hamna; Waseem, Muhammad; Hassan, Zohaib; Farooq, Raima (Pakistan Journal of Humanities and Social Sciences, 2024)
This paper investigates the generic structural potential of admission notifications of four Pakistani universities: University of Central Punjab, University of Gujrat, University of Sargodha, and University of Education Lahore. Total forty admission notifications are selected for the genre analysis in light of systemic functional linguistics. Halliday and Hasan (1989 concept of “Generic Structural Potential (GSP)” for genre analysis, served as the theoretical framework for this study. This study highlights that the admission notifications analyzed has six obligatory elements: Logo, University Name, Announcement, Respective Department, Programs Offered, and Call info and five Optional elements: Admission Schedule, Instructions, Information desk, Why Choose Us? and Scholarship and Discounts. The study posits that the GSP of advertisements of admission notifications of universities in Pakistan could be cataloged as [L^UN^]A^RD^PO^[(AS)^(I).(ID).(WCU).(S)]^CI